PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA CV TENARD JAYA DI JAKARTA SELATAN - Rani Nur Aulia; Ambar Widya Lestari (Journal of Research and Publication Innovation, 2025)
This study aims to determine the influence of work discipline and work motivation on employee performance at CV Tenard Jaya in South Jakarta.. The method used in this study is a quantitative method with a descriptive approach. The sampling technique uses saturated sampling with a population of 34 employees. The results of the study showed that work discipline has a significant effect on employee performance with the regression equation Y = 19.272 + 0.476X1. The correlation coefficient value of 0.639 means that the two variables have a strong relationship. The determination value of its influence is 0.409 or 40.9%. Hypothesis testing obtained a calculated t value> t table or (4.702> 2.03693). This means that there is a significant influence between Work Discipline (X1) on Employee Performance (Y). Work motivation has a significant effect on employee performance with a linear regression equation of Y = 15.990 + 0.572 X2. The correlation coefficient value obtained is 0.810, meaning that the two variables have a very strong relationship. The determination value of its influence is 0.657 or 65.7%. In the hypothesis test, the tcount value> ttable or (7.824> 2.03693) is obtained. This means that there is a significant influence between Work Motivation (X2) on Employee Performance (Y). Work Discipline and Work Motivation have a positive and significant effect on Employee Performance with a regression equation of Y = 14.999 + 0.086 X1 + 0.514 X2. The simultaneous correlation coefficient value obtained is 0.814, meaning that the two variables have a very strong relationship. The determination value of its influence is 0.441 or 64.1%. In the simultaneous hypothesis test, the value of f count> f table or (30.508> 2.03951) is obtained. This means that there is a significant simultaneous influence between Work Discipline (X1) and Employee Motivation (X2) affecting Employee Performance (Y) at CV Tenard Jaya.